Mussel-inspired nanoparticle composite hydrogels for hemostasis and wound healing - Cui, Guihua; Guo, Xiaoyu; Su, Ping; Zhang, Tianshuo; Guan, Jiao; Wang, Chungang (Frontiers in Chemistry, 2023)
Uncontrolled hemorrhage caused by trauma can easily lead to death. Efficient and safe hemostatic materials are an urgent and increasing need for hemostatic research. Following a trauma, wound healing is induced by various cellular mechanisms and proteins. Hemostatic biomaterials that can not only halt bleeding quickly but also provide an environment to promote wound healing have been the focus of research in recent years. Mussel-inspired nanoparticle composite hydrogels have been propelling the development of hemostatic materials owing to their unique advantages in adhesion, hemostasis, and bacteriostasis. This review summarizes the hemostatic and antimicrobial fundamentals of polydopamine (PDA)-based nanomaterials and emphasizes current developments in hemorrhage-related PDA nanomaterials. Moreover, it briefly discusses safety concerns and clinical application problems with PDA hemostatic nanomaterials.